Empirical Investigation on Attitude towards Personal Loans Borrowing - Ismail, S; Ezaili Alias, N; Koe, W-L; Othman, R; Halim Mahphoth, M (KnE Social Sciences, 2018)
In Malaysia, people enjoy various benefits provided by government such as first housing loan, medical benefit, various incentives and others. Even they obtain a lot of benefits; however, the statistics shows that the household debt keep increasing as the ratio of household debt to GDP of Malaysia increased from 62.7 percent in 2008 to 76.6 percent in 2011 and 84.6 percent in 2017. In addition, a debt service ratio of 30 percent is acceptable; however, the Malaysian household debt service ratio was 9.1 percent in 2006, rose to 49.0 percent in 2009 and dropped slightly to 47.8 percent in 2010. This indicates that approximately half of a household’s income used to pay their debts. As a result, after paying off the debt, the balance to spend on education, transport, food, and for emergencies become smaller. Additionally, an investigation of the ratio of household debt to disposable income, Malaysian ratio is 140.4 percent, and is identified as one of the highest in the world. It indicates that the loans taken are on average 1.4 times more than household income for each household in Malaysia. Therefore, the objectives of this study are to investigate the determinants that contribute to person’s borrowing loans; however, this study focus on the borrowing personal loans as it is one of main contributor to increase the household debt. Five determinants are identified which are as follows: knowledge about personal loans, media awareness, and perceptions toward personal loans, family influence and religious/ethic belief. Questionnaires were distributed to the 100 respondents. The sampling procedure adopted was stratified random sampling. The data obtained were analyzed using SPSS 20.0 which involves scale reliability, descriptive and regression analysis. The result indicates that media awareness and religious/ethic belief becomes the important determinants that influence the personal loans borrowing. Moreover, religious/ethic belief is found to be the best predictor that influences the person’s borrowing the personal loans. This study advances current knowledge by adding alternative insights to determinants of borrowing personal loans. Keywords: personal loans, media, religious, regression, household debt